2019
DOI: 10.3991/ijim.v13i06.10487
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Perceptions of Conventional Video, Virtual Reality and Augmented Reality

Abstract: <p class="Abstract"><strong>Abstract--</strong>The user’s emotional involvement plays an important role in adopting new technologies. The level of engagement with and adoption of new digital applications depends on various personal, contextual, and emotional factors. In our study, we assessed the personal factors, such as gender differences, of perceiving and adopting technologies such as virtual reality (VR), augmented reality (AR), and conventional video. Furthermore, we assessed what kind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 9 publications
3
27
0
1
Order By: Relevance
“…Previously, males were believed to be more willing to use and adapt more quickly to new technologies [ 37 ], while other studies observed no gender differences [ 38 , 39 ]. The findings of this study partially align with those of a recent study by Drin, Alamaki, and Soumala [ 40 ], which reported greater interest among females toward new technology. Novelty effects might be related to the lower usability scores of participants with previous experience; this may be related to prior experience negatively affecting attitudes toward the present experience [ 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previously, males were believed to be more willing to use and adapt more quickly to new technologies [ 37 ], while other studies observed no gender differences [ 38 , 39 ]. The findings of this study partially align with those of a recent study by Drin, Alamaki, and Soumala [ 40 ], which reported greater interest among females toward new technology. Novelty effects might be related to the lower usability scores of participants with previous experience; this may be related to prior experience negatively affecting attitudes toward the present experience [ 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…In other words, boys are more likely to use AR materials in basic design courses than girls, echoing the study of Echeverría et al [63]. Nowadays, with the development of technology, girls may be more receptive to new technologies than boys, as Dirin et al found that girls had a more positive attitude towards the experience of using new technologies (VR and AR) than boys [64]. There are no significant differences in the three factors across subjects and grades, but the mean number shows that students are generally receptive to learning with AR materials.…”
Section: Discussionmentioning
confidence: 81%
“…The relationships between the gender and user experiences of different applications are reported in another article (Dirin et al, 2019) and are thus excluded from this one.…”
Section: Discussionmentioning
confidence: 99%
“…We also ran a correlation analysis to understand the connections between all variables. The relationships between the gender and user experiences of different applications are reported in another article (Dirin et al , 2019) and are thus excluded from this one.…”
Section: Research Methods and Datamentioning
confidence: 99%